Women and The Journalist Profession (Phenomenological Study of The Professionalism of Women Journalists Within the Samarinda City Government) - Ellysa Fitri; Jaka Farih Agustian; Silviana Purwanti; Hairunnisa Hairunnisa (CV. Publikasi Indonesia, 2024)
The strategic position of journalists in the public sphere must be considered. Besides being increasingly in demand, this profession has become a promising profession and has a career path. This study aims to understand the challenges and strategies used by women journalists in the Samarinda City Government in carrying out their role as professionals. The research method used is qualitative research with a phenomenological approach, which helps to describe the reality that occurs in society. Four female journalists who met the research criteria were interviewed and observed to collect data. The results showed that women journalists in the Samarinda City Government face challenges from their surroundings. These challenges include the empowerment of normative rights that have not been optimal, difficulties in obtaining sources, including their different characteristics, the existence of fake journalists, and gender bias in the newsroom and the field. In addition, the double burden of carrying out their profession is also a problem they need help with. Despite this, these female journalists still try to maintain their professionalism. They construct themselves as professional journalists by understanding that their profession is a form of responsibility and commitment. They maintain standards of professionalism by prioritizing the code of ethics, ethical awareness, knowledge, and competencies possessed. In this way, they strive to stay relevant and in a professional carriage in the face of the ever-growing flow of news.